2010
DOI: 10.1007/s10681-010-0163-6
|View full text |Cite
|
Sign up to set email alerts
|

Potential for increasing the zinc content in common bean using genetic improvement

Abstract: A large proportion of the world's population is at risk of developing symptoms of zinc deficiency due to its low levels in food. The objective of this research was to estimate the heritability in early hybrid generations for the zinc content character in seeds of common bean (Phaseolus vulgaris L.), to investigate possible maternal effects on zinc contents and to evaluate the potential for genetic improvement. Reciprocal F 1 , and F 2 generations as well as backcross (RCP 1 and RCP 2 ) populations were produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
11
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
10
11
0
1
Order By: Relevance
“…This result indicates the absence of a maternal effect and that the seeds of the F 1 generation represent fertilization between the parents in both hybrid combinations. Our results agree with those of Possobom et al (2015) and Rosa et al (2010), who reported non-significant maternal effects for iron and zinc concentrations, respectively, in hybrid seeds of common bean.…”
Section: Genetic Variability and Maternal Effectsupporting
confidence: 93%
See 4 more Smart Citations
“…This result indicates the absence of a maternal effect and that the seeds of the F 1 generation represent fertilization between the parents in both hybrid combinations. Our results agree with those of Possobom et al (2015) and Rosa et al (2010), who reported non-significant maternal effects for iron and zinc concentrations, respectively, in hybrid seeds of common bean.…”
Section: Genetic Variability and Maternal Effectsupporting
confidence: 93%
“…Recombinants with higher and lower iron and zinc concentrations in seeds than in the parents were obtained from both hybrid combinations, similar to the results reported for other bi-parental crosses that have been carried out in common bean (Jost et al, 2009;Rosa et al, 2010;Silva et al, 2013;Ribeiro et al, 2014b;Mukamuhirwa et al, 2015;Possobom et al, 2015).…”
Section: Selection For High Iron and Zinc Concentrations In Seedssupporting
confidence: 84%
See 3 more Smart Citations